Comparison of Cognition between Elderly with Sensorineural Hearing Loss and Normal Hearing for Age - Gurung, Bikash; Rayamajhi, Pabina; Das Dutta, Heempali (Journal of Institute of Medicine Nepal, 2022)
Introduction Age related hearing loss starts at mid to late adulthood. With ageing, cognitive ability also declines. The aims of this study were to assess, compare and correlate cognition of elderly people having bilateral moderate to profound sensorineural hearing loss with the population of normal hearing for age. Methods This observational analytical study included 25 elderly participants between 55 to 75 years of age in each group; Hearing loss Group with moderate to profound sensorineural hearing loss and Normal hearing Group with normal hearing. Based on pure tone audiometry, hearing loss was classified into moderate (41-60 dB), severe (61-80 dB) and profound (81 and above). Cognition status was assessed using a Nepali version of Mini-mental state examination and classified into no cognitive impairment, mild cognitive impairment and severe cognitive impairment. Comparison and correlation of the cognitive impairment was done between the groups. Results In Hearing loss Group, 8 (32%) participants and in Normal Hearing Group, 3 (12%) participants had mild cognitive impairment. Means of total Mini-mental state examination scores between the two groups had statistically significant difference (p=0.02) but no significant correlation (Kendall tau b =0.20) between age related hearing loss and cognitive impairment was found. Conclusion Though cognitive impairment was found more in participants with age related hearing loss, there was no correlation between age related hearing loss and cognitive impairment.